Mechanism of Pleurotus Ostreatus (Oyster Mushroom) cultivation on Various Lignocellulosic wastes using empty fruit bunch, palm press fibre and corncob - Zakil, Fathie Ahmad; Ridzuan, Norida; Yusoh, K.; Shariffuddin, Jun Haslinda; Amin, Khairatun Najwa Mohd; Isha, Ruzinah; Sariah, Saalah (2017)
The utilization of low value agro-industrial waste as valuable end product has become a key research priority in the recent years. Currently, the commercial cultivation of Pleurotus ostreatus using sawdust from rubber tree as the base substrate in Malaysia has been reported. However, the price and demand of the rubber tree sawdust (RS) have been increasing, affecting the overall production cost. Thus, a new inexpensive alternative substrate yet as effective as rubber tree sawdust is needed to replace the RS as the base substrate for the cultivation of P. ostreatus. It is found that the growth and yield performance of P.otreatus are dependent on C/N ratio of the substrate. The substrates that contain empty fruit bunch (EFB), palm pressed fibre (PPF), sugarcane bagasse (SGB), corn cob (CC) in the ratio of 0.25 w/w and 0.5 w/w with rubber tree sawdust (RS) gave better the mycelium rate, fastest pinhead and fruiting bodies formations as well as the yields and BE (%) than 0.75 w/w and 1 w/w with RS and resulting the optimum C/N ratio for mushroom to growth well. The substrate of 25% PPF + 25%SGB + 50% (RS) resulting the best formulation in term of growth performance, yield and BE (%) are at 35 days for first harvest, 318.88 g/kg substrate and 79.72% respectively compared to other formulations of the substrates. However, the other combinations of the substrates also have a tremendous potential to be as an alternative substrate for mushroom cultivation in Malaysia. The particle size, C/N ratio, pH, moisture content significantly affects the growth of P. ostreatus and mineral content on the substrates. The advantages of using the biomass generated from the palm oil mills which is available throughout the year at little and no cost, and sugarcane bagasse that abundance in the rural and urban areas in Malaysia will not only solve the environmental pollution problem, but it can also offer an economically promising way to convert low quality biomasses into a valuable high protein food for human and also can help further income generation to the mushroom growers.